Additions to the flora of bryophytes of Ecuador [Adiciones a la flora de briófitas del Ecuador] - Benitez Chavez, A. (2017)
Based on a floristic study of bryophytes from southern Ecuador, we report eight species new to the country (Mastigolejeunea auriculata, Metzgeria cylindra, M. saccata, Plagiochila martiana, Porella leiboldii, Riccia crassifrons, Sematophyllum steyermarkii, Zoopsidella caledonica), nine new to southern Ecuador and several new to the provinces of El Oro, Loja or Zamora Chinchipe. Metzgeria saccata and Zoopsidella caledonica are recorded for the first time in the New World. Fissidens hydropogon and Lepidopilum caviusculum, two rare rheophytic mosses collected by Richard Spruce in the province of Pastaza (río Bombanasa) in 1857 and never seen again since, are newly reported from the province of Zamora Chinchipe (río Nangaritza). © 2011 Adac. Tous droits réservés.